2017
DOI: 10.1021/acs.joc.7b00423
|View full text |Cite
|
Sign up to set email alerts
|

Readily Accessible 1,2-Amino Ether Ligands for Enantioselective Intramolecular Carbolithiation

Abstract: A new class of chiral 1,2-amino ether ligands, readily accessible from naturally occurring α-amino- or α-hydroxy acids, was found to provide high levels of both conversion and stereocontrol (up to 95:5 er) in intramolecular carbolithiation reactions, outperforming the benchmark ligand (-)-sparteine. The ligand could be used in a substoichiometric amount (0.25 equiv) without significant loss of enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…The synthesis of candidate compounds predicted by our in silico studies was accomplished as shown in Scheme 1. Intermediate 11 was obtained starting from α‐ d ‐cyclohexylglycine ( 8 ), via a diazotization−hydrolysis reaction [28] (→ 9 ) and subsequent esterification of the carboxylic group with benzyl bromide (→ 10 ). The hydroxyl group of 10 was transformed into a good leaving group by reacting it with triflic anhydride to give donor 11 .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of candidate compounds predicted by our in silico studies was accomplished as shown in Scheme 1. Intermediate 11 was obtained starting from α‐ d ‐cyclohexylglycine ( 8 ), via a diazotization−hydrolysis reaction [28] (→ 9 ) and subsequent esterification of the carboxylic group with benzyl bromide (→ 10 ). The hydroxyl group of 10 was transformed into a good leaving group by reacting it with triflic anhydride to give donor 11 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, they have provided promising results in the enantioselective intramolecular carbolithiation, where chiral 1,2-aminoethers derived from pseudoephedrine or ephedrine 75 and, more recently, from naturally occurring a-amino or a-hydroxy acids have been employed. 76 In the latter example, both high enantioselectivity (up to 90% e.e.) and good substrate versatility in the intramolecular cyclization of aryl-allyl lithium derivatives were obtained.…”
Section: Discussionmentioning
confidence: 96%
“…amounts of the ligand. 76 This result could open the way to the development of novel catalytic procedures, thus signicantly enlarging the synthetic appeal of the reaction. A further, signicant, improvement could be provided by the use in the carbolithiations of functionalized organolithiums, [77][78][79] which would allow the construction of complex molecular systems.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] A few examples of anti-addition of alkyllithiums onto triple bonds have also been sporadically reported, however factors explaining these unexpected stereoselectivities have not yet been clearly identified. [19][20][21] In the course of our ongoing studies on the formation of carbocycles via intramolecular carbolithiation, [22,23] we took an interest in the 5-exodig cyclization of o-homopropargyl aryllithiums. Such reaction provides an access to functionalized indans, which are useful scaffolds for the development of pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%